Prinsip Keadilan Terhadap Nasabah Akibat Restrukturisasi Polis PT. Asuransi Jiwasraya - Karin Jihananda Deriyanti; Edi Wahjuni; Firman Floranta Adonara (Faculty of Law, University of Jember, Indonesia, 2022)
PT Asuransi Jiwasraya (Persero) experienced liquidity pressure so that the company's equity was recorded at negative IDR 23.92 trillion. This condition caused turmoil for policyholders to ask for clarification on this matter from PT. Asuransi Jiwasraya related to payment of insurance claims. For this reason, PT Asuransi Jiwasraya provides an alternative restructuring and based on the PT Asuransi Jiwasraya (Persero) Restructuring Acceleration Team, the number of policyholders participating in the Jiwasraya policy restructuring program until January 18, 2021 reached 102,856 participants. PT Asuransi Jiwasraya (Persero) is a BUMN where BUMN cannot be bankrupt, so the quick step taken by the government is to restructure customer policies for a new company, namely the IFG Life company. The type of research in the research used is normative juridical research, which is carried out with a statutory and conceptual approach. The result is PT. Asuransi Jiwasraya (Persero) is a step taken by the central government as the largest shareholder because it is a state-owned company. As a result of the legal restructuring of the policy on the customer, the legality of the insurance policy is no longer valid between PT. Asuransi Jiwasraya (Persero) with its customers when the customer has agreed to carry out a policy restructuring. As a result of the legal restructuring of the policy on the customer, the legality of the insurance policy is no longer valid between PT. Asuransi Jiwasraya (Persero) with its customers when her has agreed to carry out a policy restructuring. KEYWORDS: Policy, Restructuring, The Principle of Justice